The Mechanism of a Snake-Like Robot's Clamping Obstacle Navigation on High Voltage Transmission Lines. (19th September 2013) - Wei, Wang; Yu-cheng, Bai; Gong-ping, Wu; Shui-xia, Li; Qian, Chen
In this paper, the methods of a snake-like robot climbing on high voltage transmission lines are presented. The three typical locomotion modes of a snake-like robot, that is, rectilinear locomotion with a Z shaped clamping mechanism, obstacle navigation locomotion with a head part clamping mechanism and winding obstacle navigation locomotion, are discussed. The motion mechanism of the snake-like robot's head part clamping obstacle navigation is studied and the kinematics model coupled with the robot and the line environment under this mode is introduced. The position tracking algorithm and the improved algorithm of robot's clamping obstacle navigation are also proposed. Finally, the simulation experiment verifies that the improved position tracking algorithm can improve the robot's motion performance and is feasible in the robot's clamping obstacle navigation.